(untitled) (PJDOL, 2023)
The objectives of this research were to find out implementation challenges of the educational projects and policies, analyze if these policies address the issue of out of school children, and explore the parental preferences for their children’s future and concerns about the educational facilities. Cultural audit approach was adopted for identification and analysis of gaps in policies and their implementation mechanism for the enhancement of school enrolment. Ethnographic research model was used to collect field data from the government officials including policy implementers, and the parents living in the suburban areas of Islamabad.